Antibacterial Nanocarbons: Size‐Transformable Metal–Organic Framework–Derived Nanocarbons for Localized Chemo‐Photothermal Bacterial Ablation and Wound Disinfection (Adv. Funct. Mater. 33/2019). (13th August 2019) - Yang, Ye; Deng, Yiyi; Huang, Jianbo; Fan, Xin; Cheng, Chong; Nie, Chuanxiong; Ma, Lang; Zhao, Weifeng; Zhao, Changsheng
Abstract : In article number1900143, Chong Cheng, Lang Ma, Changsheng Zhao, and co‐workers develop a metal–organic framework–derived nanocarbon with near‐infrared light controlled size‐transformable capability for chemophotothermal disinfection. The unique transformation from nanodispersions to micrometer aggregations enables this nanocarbon to generate localized massive heat and abundant Zn 2+ ions for directly disrupting bacterial membrane and intracellular proteins.